A Cross-Sectional Study on the Impact of COVID-19 on Patient Confidence Regarding Dental Visits of Residents of Angeles, Pampanga Ages 18-59/Micah Mae M. Mandanas, Sandy S. Villanueva and Katrina Christine Q. Yu. - Mandanas, Micah Mae M.; Villanueva, Sandy S.; Yu, Katrina Christine Q.; Ramos, Tristan Nathaniel (2023)
INTRODUCTION: The pandemic has brought significant changes to healthcare
delivery, especially in dentistry, due to the risk of virus transmission from aerosol-
generating procedures. The study aims to determine the impact of COVID-19
pandemic on patients’ confidence regarding dental visits. It also aims to
determine the mode for each factor that has affected patient confidence in dental
visits, the proportion of patients who had visits to the dentist before and during
the COVID-19 pandemic, and the prevalence ratio of patients who had visits to
the dentist before and during the COVID-19 pandemic.
METHODS: Data from 503 respondents were collected using an online survey
questionnaire on Google Forms to determine the proportion of patients who had
dental visits before and during the pandemic, the mode for each factor that has
affected patient confidence in dental visits, and the prevalence ratio of patients
who had dental visits before and during the pandemic.
RESULTS: Results show that the participants were 4.6 times more likely to visit
the dentist before COVID-19 than during COVID-19. Several personal, social and
external factors were also analyzed through a 5-point Likert scale. Majority of x
respondents either strongly agree or agree that they do not have reservations
about going to the dentist because of the various factors examined.
CONCLUSION: Overall, the pandemic has resulted in fewer visits to the dental
clinic among Angeles residents aged 18-59, as compared to the number of visits
pre-pandemic. As the situation regarding COVID-19 evolves in Angeles, the topic
of patient confidence in dental visits is surely to be subjected to change in the
future as well.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Covid 19 pandemic .